Performance analysis of a rate adaptive multi-band ultra-wideband system based on quadrature fractal modulation scheme (Tongxin xuebao)
A rate adaptive multi-band ultra-wideband （UWB） system based on the quadrature fractal modulation （QFM） scheme was proposed.Exploring the use of homogeneous signals as modulating waveforms in UWB system,the signal within each 528MHz sub-band was divided into 8 different frequency bandwidths using wavelets transform and these data sequences to be transmitted were embedded into homogeneous waveforms.It is found that the use of homogeneous signals in such UWB system is quite feasible,leadings to a novel multi-rate diversity strategy.Within each 528MHz sub-band,the UWB-QFM system can provide much higher data rates than that of the UWB orthogonal frequency division multiplexing （OFDM） system.Simulation results also show that the bit error rate （BER） performance of the UWB-QFM system achieves a greatly improvement over existing UWB-OFDM system.Due to the fractal properties of the homogeneous signals,these data sequences to be transmitted can be recovered using arbitrarily short receiver signal.